Employability skills, personal qualities, and early employment problems of entry-level auditors: Perspectives from employers, lecturers, auditors, and students. Issue 4 (18th May 2016) - Lim, Yet-Mee; Lee, Teck Heang; Yap, Ching Seng; Ling, Chui Ching
ABSTRACT: The authors examine the issue of employability of university accounting students from the perspectives of accounting firm employers, junior auditors, accounting lecturers, and accounting students. Areas of investigation include perceived importance of employability skills and desirable personal qualities; and early employment problems encountered by junior auditors and ways to minimize the problems. The findings indicate that employers value communication skills, analytical skills, and time management skills the most. Employers prefer well-rounded and responsible individuals with positive job attitudes. The most frequently encountered early employment problems include lack of technical knowledge, difficulty in applying knowledge, and lack of English skills.